(E)‐3‐{4‐[(7‐Chloroquinolin‐4‐yl)oxy]‐3‐methoxyphenyl}‐1‐(4‐methylphenyl)prop‐2‐en‐1‐one: a ladder‐like structure resulting solely from π–π stacking interactions. Issue 7 (20th June 2014) - Montoya, Alba; Insuasty, Braulio; Cobo, Justo; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> In the title compound, C26H20ClNO3, the quinoline fragment is nearly orthogonal to the adjacent aryl ring, while the rest of the molecular skeleton is close to being planar. The crystal structure contains no hydrogen bonds of any sort, but there are two π–π stacking interactions present. One, involving the quinoline ring, links molecules related by inversion, while the other, involving the two nonfused aryl rings, links molecules related by translation, so together forming a ladder‐type arrangement